Valency-Based Topological Properties of Linear Hexagonal Chain and Hammer-Like Benzenoid. (27th April 2021) - Li, Yi-Xia; Rauf, Abdul; Naeem, Muhammad; Binyamin, Muhammad Ahsan; Aslam, Adnan
Abstract : Topological indices are quantitative measurements that describe a molecule's topology and are quantified from the molecule's graphical representation. The significance of topological indices is linked to their use in QSPR/QSAR modelling as descriptors. Mathematical associations between a particular molecular or biological activity and one or several biochemical and/or molecular structural features are QSPRs (quantitative structure-property relationships) and QSARs (quantitative structure-activity relationships). In this paper, we give explicit expressions of two recently defined novel ev-degree- and ve-degree-based topological indices of two classes of benzenoid, namely, linear hexagonal chain and hammer-like benzenoid.